Theoretical Investigation on the Magnetostatic Interaction Between Two Wire-Tube Nanostructures - Escrig-Murua, J; Riveros-Rodriguez, A (Elsevier B.V., 2017)
In this paper we have calculated analytically the magnetostatic interaction between two wire-tube nanostructures as a function of their magnetic and geometric parameters. As expected, the interaction energy increases as the nanostructures approach, but interestingly when the nanostructures are close enough, a non-monotonic behavior with the wire-tube portions is reported. Besides, we investigate the hysteresis loop for two interacting Ni81Fe19 wire-tube nanostructures by micromagnetic simulations in order to study how the interaction affects the magnetic properties of these nanostructures. This work allows for the study of magnetostatic interactions between wire-tube nanostructures that have been proposed as an interesting alternative to store information or even perform logic functions, because to their ability to pin a domain wall. © 2017 Elsevier B.V.